Shades of Empire in Late Medieval and Renaissance Reichsitalien. Questioning New Perspectives - Contel, Giovanni Francesco (Reti Medievali Rivista, 2023)
The node centered by the volume deals with the political-cultural ties between the late medieval german emperors and the plural world of the Italian humanists. Particularly, conveying a double and corresponding line of exchanges between North and South of the Alps, the point was re-focused over emperor’s presence and their retinues in the peninsula as the fulcrum of this long-term exchange. Thus, new perspectives open up regarding spaces and men involved in this political experience. Regional spaces more in contact than others with the imperial presence and the collection of sources, on the basis of macro-areas in the wake of Peter Moraw’s scheme, are very useful tools to adapt our knowledge of the multiple links between emperors and Reichsitalien, not only in the 14th century and in the previous two centuries (12th-13th) but also for the crucial subsequent period (15th-16th) – considering the entire autumn of the Medieval Empire and, at the same time, the Renaissance – still relatively little focused on by the new research fields. In order to include these centuries as well, Moraw’s thesis should be proficiently reconsidered,